Analisis Pengalaman Pelanggan dalam Membangun Kepuasan Pelanggan pada Warkop Street Kota Tangerang - Ulung Nur Wahit; Andi Agustin; Sheva Aditya Putra; Ade Fikri Mustofa (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze customer experience and customer satisfaction at Warkop Street as one of the growing culinary businesses in the community. Customer experience is an important factor because it can create positive impressions that encourage customers to revisit and recommend the place to others. Meanwhile, customer satisfaction is related to the fulfillment of customer expectations regarding the quality of services and products provided. This research uses a descriptive method with a quantitative approach. Data were collected through questionnaires distributed to Warkop Street customers. The indicators of customer experience include service competence, customer recognition, personalization, and problem solving. Meanwhile, the indicators of customer satisfaction include fulfillment of customer expectations, repeat usage, service quality, and customer loyalty. The results of this study are expected to provide an overview of how customer experience influences customer satisfaction and serve as evaluation material for Warkop Street management in improving service quality and maintaining customer loyalty.